FACILITATING ACCESS TO ACP AND AD EVIDENCE IN PALLIATIVE CARE. Issue 2 (1st June 2013) - Tieman, J; Rawlings, D
Abstract : Background: Advance care planning (ACP) and advance directives (AD) issues are significant for health professionals providing palliative care and those affected by the need for palliative care. For change to occur, existing and emerging evidence on ACP and AD needs to be accessible. While research-based evidence is being generated at ever faster rates, better infrastructure in the management of evidence-based knowledge is needed. Aim: To facilitate access to evidence-based resources related to ACP and AD. Methods: CareSearch is funded by the Department of Health and Ageing to provide evidence-based information for the palliative care community. Content is created within a knowledge translation framework. This includes identifying intended users, searching and appraising relevant literature and online resources, writing and peer review of web pages, development of evidence tools including PubMed searches, and identification of relevant materials for inclusion in the CareSearch bibliographic databases. Results: Web metrics show the website's ACP and AD materials are being used with nearly 40 000 page views in 2012. Page views by type of resource were: Clinical Practice Pages: 10 173 For Patients and Families: 9828 RAC/GP/Nurses Hub: 12 915 Finding Evidence: 5823 Discussion: Web-based resources can increase access and reach to the evidence base for ACP and AD. While access to evidence does not necessarily change practice, it is a necessary first step. Conclusion: The CareSearch website promotes evidence-based practice by facilitating access to the underlying evidence. Specific ACP and AD evidence resources and easy to read and download consumer information are available at http://www.caresearch.com.au